(untitled) (Eurasian Research Bulletin, 2023)
The abstract for the ways to improve resource tax administration in Uzbekistan is as follows: The resource tax is an important source of revenue for the government of Uzbekistan. However, there are several challenges in its administration, which can lead to revenue leakages and inefficiencies. This study aims to identify ways to improve resource tax administration in Uzbekistan by conducting a literature review of relevant studies and scholarly articles. The review reveals several key areas for improvement, including: Strengthening tax compliance measures, such as improving tax registration processes, implementing effective taxpayer education programs, and enhancing tax audit and enforcement activities, can help increase tax compliance among resource taxpayers. Streamlining tax procedures and reducing administrative burdens can contribute to more efficient resource tax administration. This can be achieved by digitizing tax processes, simplifying tax forms and documentation requirements, and improving taxpayer support services